2009
DOI: 10.3379/msjmag.0905rh0009
|View full text |Cite
|
Sign up to set email alerts
|

Heat Dissipation Mechanism for Magnetite Nanoparticle in Magnetic Fluid Hyperthermia

Abstract: We report the results of a study undertaken to determine properties of magnetite particles that dissipate heat only through Néel relaxation. The magnetite samples we considered for the heat dissipation studies were found to dissipate heat through both Néel and Brownian relaxations. The relative contributions of both relaxations on magnetic heat dissipation were investigated by analyzing the physical, magnetic, and heating characteristics of magnetite particles with various average diameters dispersed in low an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Nano-sized FeFe 2 O 4 synthesized by a chemical method has been mainly studied for this therapy. 7), 8) In our previous study, we have reported the MgFe 2 O 4 and the Mg 1¹x Ca x Fe 2 O 4 systems as materials having high heat generation ability in an AC magnetic field. 9)13) Furthermore, we found that Y 3 Fe 5 O 12 has the most superior heat ability among the reported materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-sized FeFe 2 O 4 synthesized by a chemical method has been mainly studied for this therapy. 7), 8) In our previous study, we have reported the MgFe 2 O 4 and the Mg 1¹x Ca x Fe 2 O 4 systems as materials having high heat generation ability in an AC magnetic field. 9)13) Furthermore, we found that Y 3 Fe 5 O 12 has the most superior heat ability among the reported materials.…”
Section: Introductionmentioning
confidence: 99%